DESIGNING CLASSROOM ACTIVITY: TO UNDERSTAND THE KEY PSYCHOLOGICAL PERSPECTIVES IN AN INTRODUCTORY COURSE (Proceedings of the International Conference on Education, 2018)
Introductory classes are essential for understanding any course. In a traditional class format, the instructor delivers lecture to students who passively grasps the information presented to them. However, recent researches emphasize on the importance of active student engagement in classroom for better retention. The paper presents a demonstration of class activity designed to engage students in introductory psychology course for undergraduate students. It tries to foster critical thinking and application of various viewpoints through class participation. The study took place in two sections of Introduction to Psychology course with 84 participants in Dhaka, Bangladesh. In one section, a class of one hour and thirty minutes was allocated for the activity, i.e. five groups were created to represent five Psychological perspectives, case reading and presentation was done in groups as well as question and answer round took place among each group. In another section, the case was presented to students for reading and analyzing it during their free time after class. The responses were marked from their examination scripts. The result indicates a significant difference in responses from those who took part in the class activity than those who did not. The students had better recall of elements from the case and could relate more to real life situations.
Keywords: Psychological perspectives; Classroom Activity; Introduction to Psychology course